Kontribusi Kompetensi Profesional dan Motivasi Kerja dalam Meningkatkan Kapasitas Guru Teknik Desain dan Bangunan di SMKN 1 Padang - Nazili Nazili; Danyl Mallisza (Journal on Education, 2023)
Based on the presurvey, it was found that the development the teachers’ career of design and building engineering teacher at SMKN 1 Padang was not satisfied yet. The researcher assumed that this problem occurred because of some factors, two to them were the professional competence and work motivation. The research was aimed to reveal and analyze the contribution of the professional competence and work motivation toward the development of the teachers’ career of design and building engineering teacher at SMKN 1 Padang. This research used the quantitative approach. The population of this research was all of design and building engineering teacher at SMKN 1 Padang The result of data analysis showed that the professional competence contributed significantly (13,9%) toward the development of the teachers’ career, work motivation contributed significantly (10,1%) toward the development of the teachers’ career and the professional competence and work motivation simultaneously contributed about 20,6% toward the development of the teachers’ career. Based on the result of data analysis, it could be seen that the three hypotheses were accepted empirically. The result of the research also showed that the professional competence and work motivation were two independent variables which had positive influence on the dependent variable which was the development of the teachers’ career. Therefore, the professional competence and work motivation should be improved in order to improve the development of the teachers’ career.